Charakterystyka postaci w szkole – między stereotypem a kreacją - Mirosław Grzegórzek (Problemy Wczesnej Edukacji)
Self-presentation is one of the basic human communicative behaviours. At school it is connected with the ability to characterize a character, which often results in schematic form and stereotypical content. The routinisation of procedures used by teachers breeds students’ indifference. Contemporary urge for social communication sets new challenges to the ability of characterization, one of which being the ability of effective self-presentation. In this particular context the characteristics loses its status of solely school being and faces the current urge of existence on labour market or in the virtual space. The aim of this performance is to present the results of empirical research carried out in secondary schools (against available research results of chosen “self-presentation genres” found in the Internet, such as blogs or IRC’s) in the form of quantitative-qualitative analysis of students’ abilities of the genre’s realization (complemented with the theoretical works in linguistics and linguistic efficiency development didactics) in a perspective of communicative competence’s development in this particular area.